2004
DOI: 10.1023/b:jacp.0000007582.61879.6f
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Child Interactions in Relation to Critical and Emotionally Overinvolved Expressed Emotion (EE): Is EE a Proxy for Behavior?

Abstract: Expressed emotion measures, encompassing dimensions of criticism (CRIT), and emotional overinvolvement (EOI) are increasingly being used to assess the parent-child relationship in child clinical populations, despite the lack of studies assessing their validity. We examined the correspondence between CRIT, EOI, and parent-child interactions as observed by neutral coders in a sample of 252 clinic-referred children and adolescents, ages 7-17 years. We found support for the validity of the CRIT code, with high cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
89
2
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 49 publications
7
89
2
4
Order By: Relevance
“…These findings are a unique contribution to the literature, in that prior studies have not examined relations among family environment measures using more than three assessment methods; the current investigation involved four separate methods and found convergence consistent with previous studies using two methods (e.g., McCarty, Lau, Valeri, & Weisz, 2004). Although we labeled the dimensions slightly differently, our findings regarding conceptual convergence are consistent with those of other studies of different dimensions of the family environment (e.g., Dallaire et al, 2006;Sheeber et al, 1997).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings are a unique contribution to the literature, in that prior studies have not examined relations among family environment measures using more than three assessment methods; the current investigation involved four separate methods and found convergence consistent with previous studies using two methods (e.g., McCarty, Lau, Valeri, & Weisz, 2004). Although we labeled the dimensions slightly differently, our findings regarding conceptual convergence are consistent with those of other studies of different dimensions of the family environment (e.g., Dallaire et al, 2006;Sheeber et al, 1997).…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, the mother and child selfreport constructs, the behavioral observation measures, and the speech sample indicators all converged onto their respective dimensions of positive and of negative family environment. Thus, we found empirical evidence for both methodological and conceptual convergence on these procedurally distinct measures of positivity and of negativity in the family environment.These findings are a unique contribution to the literature, in that prior studies have not examined relations among family environment measures using more than three assessment methods; the current investigation involved four separate methods and found convergence consistent with previous studies using two methods (e.g., McCarty, Lau, Valeri, & Weisz, 2004). Although we labeled the dimensions slightly differently, our findings regarding conceptual convergence are consistent with those of other studies of different dimensions of the family environment (e.g., Dallaire et al, 2006;Sheeber et al, 1997).…”
supporting
confidence: 86%
“…A high degree of correspondence has been found between EE ratings derived from the FMSS and the Camberwell Family Interview (CFI) [22,[76][77][78]. The FMSS has proven its value as a screening instrument [75,78] for measuring expressed emotion, with a satisfactory reliability [75] and validity [29,75,78].…”
Section: Assessmentsmentioning
confidence: 95%
“…EE, and specifically criticism, is thought to show these relationships in research studies because it is a good proxy measure of parenting behavior. For example, McCarty et al [2004] found that critical parents engaged in more negative parenting behaviors whereas EOI was not related to parent behavior. Daley et al [2003] also found associations between dimensions of EE and mothers' interactions with their children with ADHD.…”
Section: Ee As a General Marker Of Family Environmentmentioning
confidence: 99%